TRANSMISSION OF SHALLOT PRICE VOLATILITY IN INDONESIA - Soraya Astia Putri; Anna Fariyanti; Harmini Harmini (Faculty of Animal and Agricultural Science, Diponegoro University, 2023)
Shallots are one of the most volatile food commodities. The volatility of shallot prices can cause volatility for other commodities, coupled with the existence of shallot distribution channels in various markets, allowing volatility to flow between domestic markets. This research aims to analyze shallot price volatility and the transmission of shallot price volatility. This study uses the monthly price of shallots at the consumer level for the period January 2010 - December 2020. To analyze price volatility using the GARCH method and the transmission of volatility using the VAR method. The analysis results show that the level of volatility in the price of Indonesian shallots in East Java has the highest value, followed by DKI Jakarta, Central Java, and West Java. It was found that there is a two-way transmission of shallot price volatility in Indonesia which tends to fluctuate in the long run. Shallot price volatility in DKI Jakarta contributes to price volatility in other regions. A policy from the government is needed that is focused on stabilizing shallot prices in DKI Jakarta so that it does not spread to other region.